Only half of me: being a muslim in britain - Omaar, Rageh (Viking Books London, 2006)
'Only Half Of Me' tells the story of the author's childhood in Somalia, his family's attitude to religion, his double life as a British Muslim and that of other British Muslims. This work takes us into lives that are widely misunderstood, and tries to make sense of our own fractured world